THE INFLUENCE OF MANAGERIAL OWNERSHIP, EARNINGS MANAGEMENT, INTELLECTUAL CAPITAL, AND TAX AGGRESSIVENESS TO FIRM VALUE - Zahra, Mutia; Wulandari, Rosita; Syafrizal, Syafrizal (Universitas Pakuan, 2018)
This study aims to examine the factors that Affect the value of the company. The independent variable used is Managerial Ownership, Profit Management, Intellectual Capital and Aggressive Tax Action.This research method uses secondary data types. The sample of this research is manufacturing company of industrial sector of consumer goods listed in the Indonesia Stock Exchange. The sample was chosen by purposive sampling. The number of companies taken as the sample is 10 companies 2011-2015 period. To test the hypothesis, this study uses a significant level of 0:05, it shows that managerial ownership, management and aggressive tax earnings measures have no significant effect on firm value, while intellectual capital has a positive and significant influence on firm value. Keywords: Managerial Ownership, Earnings Management, Intellectual Capital, Tax Aggressiveness and Firm Value